Flexural behaviour of rubberised self-compacting ferro cement - Salman, Shahad Dawood (2022)
Ferro cement can be referred to as a thin wall reinforced concrete element usually having a relatively small size diameter wire mesh layers of reinforcement made from metallic or other suitable materials which are closely spaced and cast with hydraulic cement. The mesh may be made of metallic or other suitable materials. Although it has many advantages such as lightweight, easy to shape and has lower carbon footprint compared to reinforced concrete, there is a difficultly for mortar to fill and passthrough wire mesh during casting due to high volume of mesh reinforcement. Therefore, there is a need to find acceptable mix which has high degree of workability such as self-compacting mortar (SCM). The SCM can self-compact under its own weight without vibration and egregation, as well as offering much improved flow ability, filling rate, self-levelling in comparison with conventional mortar. One of the SCM technology drawbacks is its brittleness, which is greater than that of conventional mortar due to the higher cementation content and cost. This study focuses on the development of a rubberised self-compacting ferro cement mortar for use as a structural lightweight beam for low-cost construction. The study was conducted in two phases. The first phase involves the development of a suitable mix and obtain an optimum rubberised self-compacting ferro cement matrix. The developed matrix was aimed at substituting the traditional manual method of rendering of wire mesh mechanically (motorised). The suitable and optimal mortar performance was investigated in terms of its workability and strength properties. Similarly, curing by wet covering and the partial replacement of fine aggregate with crumb rubber (CR) by volume at 5% incremental level up to 20% were done. A mix ratio of 1:2, 0.38w/c, 30% pulverised fuel ash (PFA) partial cement replacement and 2.5% super plasticiser (SP) addition were determined through trial mixes until a good flow without segregation was achieved in conformity with the self-compaction requirements as per EFNARC to produce a rubberised self-compacting Ferro cement mortar (RSFM). The second phase of the study dwell on the development and investigation of the structural behaviour of the RSFM U-shape beam containing either 2 or 4 layers (2L, 4L) of rectangular or square welded wire mesh respectively. To achieve this objective, a 100 mm x 200 mm x 2000 mm U-shape beam having a constant flange of 25 mm were cast and tested. The parameters investigated includes compressive strength, flexural strength, failure mode, load-deflection behaviour, load-strain behaviour, and role of type and layers of the wire meshes. The results reveal that the incorporation of rubber crumbs decreases the workability/flow ability and strength without using pulverized fuel ash (PFA) as replacement of cement, but with 30% (PFA) of cement replacement can improve the strength with 25.61%. load and Ultimate and higher first crack loads were achieved in the beam containing Square welded wire mesh compared with rectangle welded wire mesh for the same mix. Using four layers of welded metal mesh for both type (square and rectangle) is possible due to the high workability property of the mortar, and it will obviously result in greater load carrying capacity, compared with the use of two-layer mesh. The ductility ratio percentage reduction depends on the layers, number and type of wire mesh used. In conclusion, it was found that the RSFM mix with 10% CR and reinforced with 4 layers of rectangular and square welded mesh have potential for application in channel beams which can serve as permanent forms or structural elements within a structure.